A self-paced oral feeding system that enhances preterm infants' oral feeding skills. Issue 3 (June 2015) - Lau, C.; Fucile, S.; Schanler, R.J.
Abstract: Aim: Very low birth weight (VLBW) infants have difficulty transitioning to independent oral feeding, be they breast- or bottle-feeding. We developed a 'self-paced' feeding system that eliminates the natural presence of the positive hydrostatic pressure and internal vacuum build-up within a bottle during feeding. Such system enhanced these infants' oral feeding performance as monitored by overall transfer (OT; % ml taken/ml prescribed), rate of transfer (RT; ml/min over an entire feeding). This study hypothesizes that the improvements observed in these infants resulted from their ability to use more mature oral feeding skills (OFS). Methods: 'Feeders and growers' born between 26 and 29 weeks gestation were assigned to a control or experimental group fed with a standard or self-paced bottle, respectively. They were monitored when taking 1–2 and 6–8 oral feedings/day. OFS was monitored using our recently published non-invasive assessment scale that identifies 4 maturity levels based on infants' RT and proficiency (PRO; % ml taken during the first 5 min of a feeding/total ml prescribed) during bottle feeding. Results: Infants oral feeding outcomes, i.e., OT, RT, PRO, and OFS maturity levels were enhanced in infants fed with the self-paced vs. standard bottle ( p  ≤ 0.007). Conclusion: The improved oral feeding performance of VLBW infants correlated with enhanced OFS. This study is a first to recognize that VLBW infants' true OFS are more mature than recognized. We speculate that the physical properties inherent to standard bottles that are eliminated with the self-paced system interfere with the display of their true oral feeding potential thereby hindering their overall oral feeding performance.